1983
DOI: 10.1007/bf02584215
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of the use of an ensemble average for the calculation of turbulence in pulsatile flow

Abstract: A comparison was made between turbulence calculated by subtracting an ensemble average from the instantaneous velocity and calculations made with a high pass digital filter. Velocity was measured with a laser Doppler anemometer in vitro in the region of a normal porcine aortic valve and in patients with a hot film anemometer in the region of normal aortic valves. From the velocity obtained in patients, the absolute turbulence intensity calculated using an ensemble average of 50 beats was nearly twice the turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Peak and mean velocities were traced over 10 cardiac cycles. Acquisitions were prospectively gated so that each spectral parameter calculated for each interrogation site can be averaged over 10 cardiac cycles to give an ensemble average (Walburn et al 1983). The ensemble average from 10 complete cycles was calculated for v mean , v peak and SBI, as well as the root-mean-square (RMS) deviation in the 10 contributing values for each of these parameters at each time point in the ensemble average.…”
Section: Flow Measurements Using Doppler Ultrasoundmentioning
confidence: 99%
“…Peak and mean velocities were traced over 10 cardiac cycles. Acquisitions were prospectively gated so that each spectral parameter calculated for each interrogation site can be averaged over 10 cardiac cycles to give an ensemble average (Walburn et al 1983). The ensemble average from 10 complete cycles was calculated for v mean , v peak and SBI, as well as the root-mean-square (RMS) deviation in the 10 contributing values for each of these parameters at each time point in the ensemble average.…”
Section: Flow Measurements Using Doppler Ultrasoundmentioning
confidence: 99%
“…Several methods which account for cycle-to-cycle variation have been used to calculate the mean periodic velocity (Rask 1981, Walburn et al 1983, Liou & Santavicca 1985. In each case, some technique is used to identify the mean pulse.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…In the latter, a digital low-pass filter was used to separate the mean periodic signal of each cycle from the turbulent fluctuations. This filter technique is similar to that of Walburn et al (1983) for determining the mean periodic signal. However, Walburn et al reported turbulent…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Turbulence is one such hemodynamic phenomenon that is of particular interest, as it has been shown that turbulence near vessel stenoses have been implicated as a risk for thromboembolic stroke [4] and as a potential indicator of significant stenoses [8,9]. The most popular method for quantifying turbulence by Doppler ultrasound is turbulence intensity (TI), which directly measures incoherent fluctuating velocity components [10][11][12][13]. It is possible to quantify TI through ensemble averaging or through frequency filtering methods, where both of these analytical methods are used to decompose the Doppler signal into coherent pulsatile fluctuations and incoherent turbulent fluctuations.…”
Section: Introductionmentioning
confidence: 99%